Exploring internal structures and properties of terpolymer fibers via real-space characterizations - Michael R. Roenbeck; Kenneth E. Strawhecker (Beilstein Journal of Nanotechnology, 2023)
While significant research has investigated the processing and properties of high-performance terpolymer fibers, much remains to be understood about the internal nano- and microstructures of these fibers, and how these morphologies relate to fiber properties. Here we use a focused ion beam notch technique and multifrequency atomic force microscope mapping to characterize the internal structure and local mechanical properties within Technora® fibers. We find a highly fibrillated structure that appears to connect with both the fiber’s molecular chemistry and full-fiber mechanical properties. In addition, through detailed comparisons with Kevlar® K29 fibers, we find remarkable differences between the internal structures of the two fibers, and posit connections between our measurements and multifunctional performance studies from the literature.